Funções executivas de crianças de escola pública em fase inicial de alfabetização - Wanderley, Bruna Cardoso (2019)
Executive functions (FE) are a set of cognitive and/or emotional skills recruited in situations which automatic or instinctive responses are not sufficient. To use them requires some effort. Crucial to achieve healthy cognitive development in individuals they are related to reasoning, problem solving and planning. In addition, they contribute to academic, family and social success. The developmental characteristic of EF favors childhood as the ideal phase for the effective development of these skills by having the cognitive potential of children available. Therefore, schools represent opportune spaces for researching and development of these skills. Thus, the objective was to analyze the performance of EF in the domains working memory, cognitive flexibility, inhibitory control, planning and verbal fluency. Seventy children from the 1st to the 3rd grade of elementary school enrolled in the municipal school of Natal/RN participated in the study, so that each school year constituted three distinct assessment groups. The study is quantitative, cross-sectional and approved by the Ethics Committee under protocol CAAE No. 85607718.0.0000.5537. The Diamond Model (2013) was elected for the theoretical understanding of the construct. Data were treated by descriptive and inferential analysis, with normal distribution of the sample, using one-way ANOVA statistical tests, with Bonferroni post-hoc and Pearson r tests. Overall, the results indicated that the descriptive measures of EF increased with school progression, however, only verbal fluency demonstrated significance between the 2nd and 3rd years. The others indicated significance between the 1st and 2nd and/or between the 1st and 3rd years. Therefore, the study contributed to the discussion about the development of EF in the early years of literacy.